APLICATION OF ELECTROCOAGULATION METHOD TO REDUCE HYPOCHLORITE IONS LEVELS IN THE WATER POOL WITH ALUMINUM-GRAPHITE ELECTRODE - Ari Astuti; Suyanta Suyanta (Universitas Negeri Yogyakarta, 2018)
AbstractThis study aims to determine the optimum potential and optimum time of elektrocoagulationprocess, with aluminum and graphite electrodes to reduce hypochlorite ions form the water pool anddetermine the concentration of hypochlorite ions before and after electrocoagulation process. Thesubject of this research was optimum electric potential and optimum time of electrocoagulationefficiency against hypochlorite reduction. The Object of this research was hypochlorite ions in poolwater Hercules Maguwoharjo Yogyakarta. The Optimization of the electrical voltage was done onvariation 4, 6, 8, 10, and 12 volts and optimization of the time electrocoagulation process was doneon variations 2, 4, 6, and 8 hours. Parameters used are concentration of hypochlorite ions in thewater. The Effectiveness of electrocoagulation was seen from the graph of changes in theconcentration of hypochlorite ions after electrocoagulation process. The determination ofhypochlorite content was using uv-vis spectrophotometry with wavelength 556 nm. The resultsshowed that the highest electric potential is 12 volt and the longest time of electrocoagulation processis 8 hours. The Use of electrocoagulation method for pool water treatment effectively decreases theconsentration of hypochlorite ions.Keywords : elektrocoagulation, hypochlorite, aluminum, graphite.